Deforestation in Conservation Units of the Brazilian Amazon: the case of the Terra do Meio Mosaic - Jesus, Silvia Cristina de; Catojo, Adriana Maria Zalla (Ciência e Natura, 2020)
The Terra do Meio Mosaic in the Brazilian Amazon was created with the purpose of inhibiting illegal logging and gold mining, as well as land grabbing, cattle raising and other activities that promote deforestation in the region. This work analyzes the dynamics of the deforestation (clear-cutting) in this set of Conservation Units and how they contain deforestation in the region. These protected areas have been shown as an efficient tool in conserving natural ecosystems, with maintenance of main forest cover. The exception is the Triunfo do Xingu Environmental Protection Area which has less power to contain deforestation because it is a category that involves private lands. Na important reason for the clear cut of the forest is the establishment of pasture for cattle breeding. In the municipalities that contains the Mosaic, the small properties (up to 4 fiscal modules) are the ones that present the highest proportion of deforestation. The Indigenous Lands also play an important role in the maintenance of the Conservation Units functioning as a protective boundary zone and in refraining the clear-cutting, which occurs mainly in the surroundings of rivers and roads.